2011
DOI: 10.1016/j.athoracsur.2010.08.055
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Lung Transplantation Offers Better Long-Term Survival, Compared With Single-Lung Transplantation, for Younger Patients With Idiopathic Pulmonary Fibrosis

Abstract: Background Single-lung transplantation (SLT) and bilateral lung transplantation (BLT) are both good options for patients with end-stage lung disease secondary to idiopathic pulmonary fibrosis. It is, however, unclear whether BLT offers any survival advantage over SLT. The purpose of our study was to evaluate a large group of patients to determine if either SLT or BLT officered a long-term survival advantage for patients with IPF. Methods This was an Institutional Review Board-approved retrospective analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 15 publications
5
47
0
4
Order By: Relevance
“…Survival after LTX in IPF in our study is longer than previously published survival data [4,5,7,[21][22][23][24]. Neurohr and colleagues reported similar good survival after LTX in IPF patients, but only in the patients who received BLT [17].…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Survival after LTX in IPF in our study is longer than previously published survival data [4,5,7,[21][22][23][24]. Neurohr and colleagues reported similar good survival after LTX in IPF patients, but only in the patients who received BLT [17].…”
Section: Discussionsupporting
confidence: 46%
“…Furthermore, Force and colleagues recommended that BLT should be considered in IPF patients younger than 57 years [21]. Of note, recently reported data from the ISHLT also showed a probable long-term survival advantage for BLT in IPF [7].…”
Section: Discussionmentioning
confidence: 96%
“…It has become clear from the data in the ISHLT Registry that BLTx in these patients is associated with better long-term survival compared with SLTx, a finding now corroborated by many groups [4,5,14,20], including ours [21]. Improved long-term survival after BLTx in patients with emphysema may in part be due to the lower rates of BOS and a longer decline in pulmonary function over time once BOS develops [22].…”
Section: Discussionmentioning
confidence: 50%
“…As demonstrated in Table 1, our transplant group has gradually moved from SLTx to BLTx, with now nearly 90% of our recipients receiving two donor lungs. SLTx is now reserved for patients mainly with pulmonary fibrosis and who are older than 60 years [5]. A recent analysis of the UNOS database has shown that survival after BLTx and SLTx was comparable in patients 60 years of age and older [25].…”
Section: Discussionmentioning
confidence: 98%
“…Even at a simpler level, the dilemma is illustrated by the potential to perform SLT in many patients with interstitial lung disease or emphysema. Double lung transplantation undoubtedly results in better physiological outcomes, but not universally superior survival [59,60]. However, the overall utility is better if SLT is performed where possible (most years of survival from the total donor pool) [60,61].…”
Section: Perfusion Solutionsmentioning
confidence: 99%